P-212 Systematic Review: Fecal Microbiota Transplantation in the Treatment of Pediatric Gastrointestinal Diseases. (March 2016) - Mosby, Danielle; Lopresto, Bailey Ingraham; Bacon, Alfred; Levy, Susan
Abstract : Background: Inflammatory Bowel Disease (IBD) is diagnosed during childhood in 25% of cases. Characterized by chronic inflammation of the intestinal tract, current theories suggest that genetics, environment, or diet contributes to the development of IBD. In addition to a reduced quality of life, potential complications include colon cancer, bowel obstruction, and osteoporosis. Difficulty in treating IBD and associated therapeutic toxicity has motivated efforts to identify and implement new treatments, including fecal microbiota transplantation (FMT). This systematic review seeks to describe the current state of FMT as a potential treatment within the diagnosed pediatric population. Methods: Studies were retrieved from PubMed, Ovid, EMBASE, EBSCOHost, and Web of Science, which reported on one or more cases of FMT for children (ages 0–21) between 1985 and 2015. Additional cases were identified through a review of the gray literature and direct outreach to clinical providers. Results: The search strategy yielded 7 studies on the use of FMT in treating IBD. The median age of the patient population was 15 years old (total n = 32, 18 male). The population included 72% (23/32) patients with ulcerative colitis (UC), in addition to 9 patients with Crohns disease (CD) (all from a single study). Over 50% (17/32) of patients were diagnosed with IBD over 1 year prior to study periods. Most commonly used previous medications included steroidal treatment, mesalamine, and 6-MP (47%, 28%, and 22% respectively) and were not mutually exclusive. A quarter of patients (8/32) saw extended remission and no relapse during the follow-up period, which varied between 4 to 38 weeks. Patients with one to 5 infusions saw better results (more frequent remission without relapse) than children who received 6 or more infusions (29% [7/24] versus 13% [1/8], respectively), though not significant ( P -value = 0.28). Among the 9 patients with CD, 44% (4/9) had more remissions without relapses during their 12-week follow-up than patients with UC (17% [4/23]) whose follow-up was between 4 and 38 weeks. However, this difference was not significant ( P -value = 0.18). Extensive variation was seen between each study protocol, specifically in FMT solution preparation (stool to saline ratio, amount administered, and number of infusions), and donor selection and screening. More than half of donor stool information was missing (18/32) and 71% (10/14) of patients with available donor information received stool from a family member. Although all donations were screened for Clostridium difficile, sexually transmitted diseases, and some ova or parasites, less than half were screened for a history of gastrointestinal disease (15/32). Conclusions: This review identified and analyzed current published studies reporting FMT as a treatment for IBD in the pediatric population. A quarter of patients saw extended remission, and given that IBD is a chronic life-long condition, any form of remission may prove to be beneficial to individuals afflicted. Further investigation is necessary to standardize FMT procedures and screening processes, and future studies need to adopt uniform methods with robust populations for adequate analysis.